A Study Of Computer Knowledge Among Higher Secondary School Teachers In Aizawl City In Relation To Teaching Experience And Type Of School Management (International Journal of Food and Nutritional Sciences, 2022)
The present study seeks to determine the level of computer knowledge among higher secondary school teachers in Aizawl city in relation to their teaching experience and type of school management. The study comprised of 150 sample of higher secondary school teachers within Aizawl city selected by using simple random sampling. The findings revealed that there is no significant difference in the level of computer knowledge of higher secondary school teachers in relation to their teaching experience and in relation to type of school management. Computer Knowledge Test (CKT) developed by Dr. Ananthula Raghu and Dr. S. Mahendar Reddy in the year 2017 was used.